The nucleocapsid of the lipid-containing double-stranded RNA bacteriophage phi 6 contains a protein skeleton consisting of a single polypeptide species. - Olkkonen, V M (1987)
The nucleocapsid of the enveloped double-stranded RNA bacteriophage phi 6 was isolated by extraction with the nonionic detergent Triton X-114 and subjected to disruption analysis with chelating and protein-denaturing agents. The subnucleocapsid particles were separated in rate-zonal sucrose gradients, and their ultrastructure and protein composition were analyzed. The role of divalent cations in the nucleocapsid structure was studied by using a precipitation assay of the isolated nucleocapsid proteins. The phi 6 nucleocapsid had a cagelike skeleton consisting of a single polypeptide species (P1). Two other proteins (P2 and P4) were associated with the P1 cage. These three early proteins were previously known to be involved in the RNA synthesis machinery of the virus. The stability of the nucleocapsid surface lattice consisting of protein P8 was dependent on Ca2+ ions.